Oral health awareness among Penang Matriculation students / Nur Ezzati Abdul Hamid - Abdul Hamid, Nur Ezzati (Bachelor of Science (Hons.) Statistics, 2015)
Oral health awareness is the individual or collective alertness to the existence and prevention of oral disease and the steps to obtain treatment for these diseases when it occur. According to Assistant Public Health Minister “Very often, these problem (around 60 to 90% of students worldwide suffer dental caries) are mainly due to ignorance, which may in turn is attribute to poor education and lack of information. Ministry of Health (MOH) stated that Oral Health is important because of its connection to other disease and also stressed that oral problem can impact self-esteem and lead to problem such as eating, speaking and learning. The aim of this study was to assess the knowledge, attitude and behavior of Matriculation Students toward oral health awareness as well as to evaluate the factor that determines these variables. Students of Penang Matriculation college (n=307) of an average age of 19 years attending college in Penang were recruited into this study. The subjects completed a questionnaire that aimed to evaluated teenagers behavior, attitude and knowledge that affects the oral health awareness. In this study, the result shows that there is significant relationship between student’s attitude and their level of awareness of oral health and no significant relationship between knowledge and behavior towards oral health awareness. While there is no significance different between knowledge, attitude and behavior when they are classified according to their gender. This study were analyzes using independent sample of t-test and structural equation modeling (SEM)